Synthesis, Characterization, and Pharmacodynamics Study of Enrofloxacin Mesylate - Pei L; Yang W; Fu J; Liu M; Zhang T; Li D; Huang R; Zhang L; Peng G; Shu G; Yuan Z; Lin J; et al. (Dove Medical Press, 2020)
Lin-lin Pei,1,* Wen-zhu Yang,1,* Jing-yuan Fu,1,* Meng-xi Liu,1 Ting-ting Zhang,1 Dong-bo Li,1 Ruo-yue Huang,1 Li Zhang,1 Guang-neng Peng,1 Gang Shu,1 Zhi-xiang Yuan,2 Ju-chun Lin,1 Wei Zhang,1 Zhi-jun Zhong,1 Ling Zhao,1 Hua-lin Fu1 1Department of Pharmacy, College of Veterinary Medicine, Sichuan Agricultural University, Chengdu, Sichuan, People’s Republic of China; 2College of Pharmacy, Southwest Minzu University, Chengdu, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hua-lin FuDepartment of Pharmacy, College of Veterinary Medicine, Sichuan Agricultural University, Chengdu, Sichuan 611130, People’s Republic of ChinaTel +86 028-86291162Email fuhl2005@sohu.comIntroduction: Enrofloxacin is used in the treatment of a wide variety of bacterial infections in mammals. However, its poor solubility limits the clinical use.Methods: In order to improve the solubility of enrofloxacin, the enrofloxacin mesylate (EM) were obtained by a chemical synthesis method. The characterization of EM was carried out using ultraviolet scan (UV), synchronous thermal analysis (SDT), fourier transform infrared spectrometer (FTIR) and mass spectrometry (MS), nuclear magnetic resonance (NMR) and X-ray powder diffraction analysis (XRPD). Acute toxicity of EM in Kunming mice was studied. Besides, pharmacokinetic studies were performed in New Zealand rabbits at a single oral dose of 10 mg/kg, and the antibacterial activity of EM was also evaluated.Results: EM was successfully synthesized and purified. The stoichiometric ratio of mesylate to enrofloxacin was 1:1 and the aqueous solubility of EM was 483.01± 4.06 mg/mL, the solubility of EM was about 2000 times higher than enrofloxacin. The oral lethal dose (LD50) of EM was 1168.364 mg/kg, and the pharmacokinetics indicated that the oral relative bioavailability of EM was about 1.79 times and 1.48 times higher than that of enrofloxacin and enrofloxacin hydrochloride, respectively. In addition, the in vitro antibacterial activity of EM was not significantly changed compared with enrofloxacin and enrofloxacin hydrochloride.Conclusion: EM has higher solubility, low toxicity for oral use, and increases the oral bioavailability in rabbit. This study may be of benefit for the development of new enrofloxacin drugs.Keywords: enrofloxacin mesylate, characterization, antibacterial effect, acute toxicity, pharmacokinetics